The Time factor in aphasic evaluation - a pilot study on the w.a.b. - Jyothi Balgi and Prathibha Karanth (Journal of All India Institute of Speech and Hearing, 1970)
General slowing in performance, longer reaction time etc., are often considered as some of the nonspecific symptoms present among the aphasics. Most of the aphasic tests batteries are power tests rather than speed tests. As a result subtle disturbances of timing may be missed. The present study introduces the aspect of timing, to determining whether slowing of performance attributed to normal aging is evident on the Western Aphasia Battery or not and to compare normals with aphasics. Results of this pilot study reveal a significant difference between the normals and aphasics on total time required and a negative correlation was foundto exist between severity of aphasia, determined in terms of Aphasia Quotient (A. Q.) and timing aspect.